Touch Crossing-Based Selection and the Pin-and-Cross Technique - Luo, Yuexing (University of Waterloo, 2015)
This thesis focuses on the evaluation, exploration and demonstration of crossing paradigm with touch modality. Under the scenario of crossing selection, the target is selected by stroking through a boundary 'goal' instead of pointing inside a perimeter. We present empirical evidence to validate crossing performance for touch. Inspired by the experimental results, we then develop, evaluate and demonstrate a new unimanual multi-touch interaction space called 'pin-and-cross'. It combines one or more static touches ('pins') with another touch to cross a radial target, all performed with one hand. Our work serves to provide necessary support for the exploration and evaluation of more expressive multi-touch crossing techniques.
Keywords: touch; crossing; interaction technique; menus; user interfaces; Computer Science